A Late Pleistocene palynoflora from the coastal area of Songkhla Lake, southern Thailand. - Wipanu, Rugmai (ScienceAsia, 2016)
A sediment sample dating from the Late Pleistocene from Ban Bo So, Singha Nakhon district, Songkhla province, in the Sathingpra Peninsula of southern Thailand was extracted for palynological study. The predominance of mangrove palynomorphs, which are from various families including Rhizophoraceae, Sonneratiaceae, and Avicenniaceae, infers a marine deposit in a tidal environment. Other pollen is representative of tropical plants in back mangrove forest, beach forest, swamp, and lowland-montane forest. The presence of a mangrove community is indicative of a high sea level whereas inland pollen types suggest a tropical vegetation.